Effect of 20-OH ecdysone and methyl farnesoate on moulting in the freshwater crab Travancoriana schirnerae. Issue 4 (2nd October 2019) - Raghavan, Sudha Devi Arath; Ayanath, Aswani
ABSTRACT: This study elucidated the impact of 20-OH ecdysone (20E) and methyl farnesoate (MF) administration on moulting in the edible freshwater crab Travancoriana schirnerae . Crabs in intermoult and early premoult stages were introduced with different doses of 20E and MF and observed the reduction in intermoult and premoult intervals, total moult cycle duration, incidence of ecdysis, mortality and survival rate. Administration of 20E and MF at intermoult stages caused a significant reduction in the intermoult intervals as compared to the control groups, but no significant reduction in the premoult intervals except in crabs treated with 30 and 50 ng 20E and 50 ng MF at C4 stage of intermoult. Injection of 20E and MF during early premoult stages significantly shortened the premoult intervals. The 20E-treated crabs showed significantly shortened intermoult and premoult intervals, moult cycle duration, percentage reduction in moult interval (MI) and increased incidence of moult than MF-treated crabs. Incidence of deaths found apparently high in MF-treated groups than 20E-injected groups and at higher concentrations than at low and medium concentrations. To conclude, both 20E and MF were effective in inducing proecdysis and ecdysis in T. schirnerae, but 20E is more effective in inducing proecdysis and ecdysis than MF.